RECONSTRUCTION OF BULLYING THERAPY FROM THE PERSPECTIVE OF THE QURAN - Rida Hayati Rida; Irman Irman; Jumli Sabrial Harahap; Irma Suryani Nasution (Universitas Negeri Surabaya, 2025)
Bullying is a negative behavior that can hurt someone physically and mentally. This research aims to explain therapy that can be used to reduce bullying behavior from an Islamic perspective. The method used in this research is a qualitative literature study approach. Literature study obtained from several sources such as articles, books, theses, magazine theses and others. The results of this research include several suras related to the counseling process in overcoming bullying, including surah Al-Hujrat verses 11 and 13, surah An-Nisa verse 46, Al-A'raf verse 126 and Ash-Shura verse 43. Al-Qur' This is the main basis for counselors in solving problems experienced by clients, especially regarding bullying problems which need to be addressed from the smallest things. Clients who bully others will exhibit immoral behavior or actions. Keywords: Therapy, Bullying, Al-Qur'an.